1999
DOI: 10.1016/s0893-133x(98)00056-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Neuroendocrine Responses to Meta-Chlorophenylpiperazine (m-CPP) but Normal Responses to Ipsapirone in Marathon Runners

Abstract: Several clinical studies suggest antidepressive and anxiolytic effects of regular aerobic exercise. To study the effects of exercise on central serotonergic receptor sensitivity, we performed neuroendocrine challenges using oral doses of meta-chlorophenylpiperazine (m-CPP, 0.4 mg/ kg), ipsapirone (0.3 mg/kg) and placebo in 12 marathon runners and 12 healthy controls not practicing regular exercise. After administration of the nonselective serotonergic agonist m-CPP, which exerts a number of wellreproducible ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 79 publications
(105 reference statements)
0
31
0
2
Order By: Relevance
“…Rodents with wheel access typically show a more finely tuned response to stressors, mounting a more robust response than sedentary animals to those with physical components such as forced swim or restraint that would demand sufficient mobilization of energy resources (Campbell et al, 2009;Droste et al, 2007;Droste et al, 2003;Droste et al, 2006), and a more curtailed response to those that are purely psychogenic, such as loud noise or novel cage exposure that would require less energy Droste et al, 2007;Droste et al, 2003). A similar finding is observed in humans in that exercise blunts the HPA-axis response to a single exposure of oral mCPP a 5HT-2C agonist with anxiogenic properties (Broocks et al, 1999;Broocks et al, 2001). Taken together, these findings suggest that exercise may improve control over the HPA-axis response to stress, producing a more efficient response that is enhanced or diminished depending upon the nature of the stressor.…”
Section: Discussionmentioning
confidence: 60%
“…Rodents with wheel access typically show a more finely tuned response to stressors, mounting a more robust response than sedentary animals to those with physical components such as forced swim or restraint that would demand sufficient mobilization of energy resources (Campbell et al, 2009;Droste et al, 2007;Droste et al, 2003;Droste et al, 2006), and a more curtailed response to those that are purely psychogenic, such as loud noise or novel cage exposure that would require less energy Droste et al, 2007;Droste et al, 2003). A similar finding is observed in humans in that exercise blunts the HPA-axis response to a single exposure of oral mCPP a 5HT-2C agonist with anxiogenic properties (Broocks et al, 1999;Broocks et al, 2001). Taken together, these findings suggest that exercise may improve control over the HPA-axis response to stress, producing a more efficient response that is enhanced or diminished depending upon the nature of the stressor.…”
Section: Discussionmentioning
confidence: 60%
“…Both 5-HT2C antagonists (SB 242084) and inverse agonists (SB 206553) possess anxiolyticlike properties in animal models of anxiety (Kennett et al, 1996(Kennett et al, , 1997. 5-HT2C receptor down-regulation following chronic exercise (Broocks et al, 1999), and desensitization in response to SSRI-treatment (Questad et al, 1997), have been proposed as the mechanisms by which these two treatments are anxiolytic.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Broocks et al (Broocks et al 1999) compared neuroendocrine challenge in marathon runners and controls and showed that a blunted cortisol response to m-CPP 0.4 mg/kg, but not to ipsapirone 0.3 mg/kg, differentiated the marathon runners from controls. Broocks et al (2000) also reported a study of neuroendocrine challenge with m-CPP and ipsapirone in groups of patients with panic disorder and/ or agoraphobia and controls.…”
mentioning
confidence: 99%